SIRT1-dependent myoprotective effects of resveratrol on muscle injury induced by compression - Sin, Thomas K.; Yung, Benjamin Y.; Yip, Shea P.; Chan, Lawrence W.; Wong, Cesar S.; Tam, Eric W.; Siu, Parco M. (Frontiers in Physiology, 2015)
Our current understanding on the molecular mechanisms by which sustained compression induces skeletal muscle injury is very limited. This study aimed to test the hypothesis that activation of SIRT1 by the natural antioxidant resveratrol could deactivate apoptotic and catabolic signalling in skeletal muscle exposed to moderate compression. Two cycles of 6-hour constant pressure at 100 mmHg was applied to the tibialis region of right, but not left hindlimbs of Sprague Dawley rats pre-treated with DMSO (vehicle control) or resveratrol with/without sirtinol. Skeletal muscle tissues lying underneath and spatially corresponding to the compressed sites were collected for analyses. Resveratrol prevented the compression-induced manifestations of pathohistological damages including elevations of the number of interstitial nuclei and area of interstitial space and ameliorated oxidative damages measured as 4-hydroxy-2-nonenal (4HNE) and nitrotyrosine in skeletal muscle. In parallel, resveratrol augmented the expression level and activity of SIRT1 and phosphorylation levels of Foxo3a and Akt while suppressed the increases in protein abundances of p53, Bax, MAFbx and ubiquitin, enzymatic activities of caspase 3 and 20S proteasome, and apoptotic DNA fragmentation in the compressed muscle. These favourable myoprotective effects of resveratrol were diminished upon pharmacological blockade of SIRT1 by using sirtinol. These novel data support the hypothesis that the anti-apoptotic and anti-catabolic effects of resveratrol on compression injury in skeletal muscle required the action of SIRT1.